The Relevance of Progressive Law in Legal Reasoning in Indonesia - Vincentius Patria Setyawan (Faculty of Law, Universitas OSO, 2025)
Legal reasoning in Indonesia often faces challenges in achieving substantive justice due to rigid and textual interpretations of the law. Progressive law, introduced by Satjipto Rahardjo, offers a more dynamic and humanistic legal approach, emphasizing law as a tool for social change rather than merely a set of normative rules. This perspective is particularly relevant in addressing contemporary legal issues in Indonesia, where formalistic legal interpretations sometimes fail to deliver justice. This study aims to analyze the relevance of progressive law in shaping legal reasoning in Indonesia. It seeks to explore how the principles of progressive law can contribute to a more responsive and justice-oriented legal system. This study employs a normative legal research method with a conceptual approach. It examines primary and secondary legal sources, including legal doctrines, jurisprudence, and relevant literature, to understand the theoretical and practical implications of progressive law in Indonesian legal reasoning. The study finds that progressive law provides a necessary paradigm shift in Indonesian legal reasoning by encouraging judges and legal practitioners to go beyond rigid legal texts and consider social realities. It highlights that legal reasoning based on progressive law can bridge the gap between law in books and law in action, fostering legal decisions that better reflect societal needs and justice. However, challenges remain in its application, particularly in balancing legal certainty and judicial discretion. The incorporation of progressive law principles in legal reasoning can enhance the Indonesian legal system’s responsiveness to societal dynamics. Further research and judicial training are needed to optimize its implementation for a more just legal order.